Literature Review : Faktor-Faktor Dan Pengaruh Motivasi Kerja Terhadap Kinerja Pegawai - Maratus Solikah; Diana Enggar Pradita; Gita Iranie F.S; Nurul Aini; Muallimin Muallimin (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This study aims to comprehensively examine the role of management psychology in the dynamics of group work within organizational settings. Management psychology integrates psychological principles with managerial strategies to understand, guide, and manage individual behaviors in groups, aiming to foster harmonious collaboration and optimal productivity. Using a literature review approach, this study analyzes various academic sources including peer-reviewed journals, scholarly books, and previous research relevant to the topic. The findings indicate that several psychological factors—such as open interpersonal communication, participative leadership styles, appropriate motivational strategies, and effective conflict resolution—play a critical role in shaping team performance and cohesion. Leaders who are able to understand the emotional conditions, psychological needs, and potential of each team member can create a supportive and positive work environment that encourages engagement and shared goals. Moreover, clarity of roles, recognition of individual contributions, and the cultivation of a sense of belonging within the organization further strengthen team dynamics. This study recommends the implementation of organizational psychology training for managers and team leaders to enhance their ability to manage group interactions wisely, adaptively, and humanely. By applying psychological insights in group management, organizations can improve overall effectiveness through strong collaboration, mutual respect, and collective commitment.